Evaluating strategies planning the reconstruction of devastated cities using analytic hierarchy approoach City of Ramadi, a model - Thaer Shaker Mahmoud, Dr. (Iraqi Journal of Civil Engineering, 2017)
The appropriate planning policies for the reconstruction and rehabilitation of devastated towns and cities have a role prominent and important in the activation of spatial development processes where appropriate to give the selected positive results in the reconstruction and improvement of the previous methods in this area. From this point the quest is considering the possibility of choosing planning policy objective and proposed for the reconstruction and rehabilitation of the city of Ramadi to what came to him from the devastation and destruction as a result of the military operations that took place for the period from 2013 -2016 and the belief of the argument (requires the success of the military operations that accompanied the success of the processes of reconstruction being the mutually reinforcing) it was proposed three development policies is the policy of modernization and urban renewal policy and re-new residential neighborhoods and the policy of pairing between the old and new planning, taking into account the future expansion.The study found after using the method of quantitative analysis (method Analytical Hierarchy Process AHP) as a way diagram of the calendar that the third policy is a combination of old and new planning policy taking into account the urbanization of the city is the best among the proposed development policies, and having been using direct questionnaire segment of experts and specialists affairs planning as representing stakeholders and Shan has been used as a way of governing and the officer to know the credibility and reliability in the accuracy of the results of the quantitative hierarchical analysis.